ANALISIS USABILITY TERHADAP USER EXPERIENCE PADA WEBSITE KHARISMA CLASSROOM MENGGUNAKAN METODE USE QUESTIONNAIRE - Ornardo, Bryant; Rahman, Syaiful; Arianti (STMIK KHARISMA Makassar, 2024)
This study aims to analyze the usability of the user experience of the Kharisma Classroom website based on user experience using the USE Questionnaire method. This method has 4 aspects, namely Usefulness, Ease of Use, Ease of Learning, and Satisfaction. The study began by using questionnaires via google form as a data collection tool, then distributed to 33 respondents, then continued by testing the validity of the data to analyze the data resulting in 23 items of questions worth processing. After that, it continued by testing the data rehabilitation of 23 question items by generating a Cronbach's Alpha value of 0.876. The results of this study include 4 aspects of use questionnaire, in the form of usefulness aspect with a percentage of 92.12%, ease of use aspect with a percentage of 91.11%, ease of learning aspect with a percentage of 91.21%, and satisfaction aspect with a percentage of 90.53%. Thus, for the overall results of this study has a percentage of 91.15% (very worth), so it can be concluded that the Kharisma Classroom website has met the standards or criteria in the USE Questionnaire method.